Occupational therapy for physical dysfunction - Trombly, Catherine Anne, ....- (Baltimore (Md.) : Williams and Wilkins, 1995)
Contents: --------- 1. The practice of occupational therapy for physical dysfunction 2. Assessment 3. Therapeutic mechanisms 4. Treatment principles and practices 5. Adjunctive therapies 6. The practice of occupational therapy for selected diagnostic categories
Keywords: Ergotherapie; Handicapped; Occupational Therapy; Occupational therapy; People with disabilities -- Rehabilitation